Practical Theology and Missiology – Can They Live Together?. Issue 2 (29th May 2014) - Rooms, Nigel; Ross, Cathy
Abstract : The relationship between the academic disciplines of practical theology and missiology is explored critically in this soap box article. Their commonalities and differences are rehearsed and a case is made for their "living together" in a fruitful and creative relationship, not least because of the worldwide perspective that missiology carries with it.